Efek Protektif Nigella sativa Terhadap Karsinogenesis Sel Ginjal Tikus yang Diinduksi 7,12-dimetilbenz(a)antrasena (DMBA) - DIAH AYU ANDINI; HANIF NASIATUL BAROROH; HENY EKOWATI (Fakultas Farmasi Universitas Pancasila, 2013)
Black cumin (Nigella sativa) is known to have anticancer activity. Previous study showed that chloroform extract of N. sativa, have cytotoxic activity on T47D cell line. The purpose of this study was to determine the antiproliferation activity of chloroform extract N. sativa in female rats induced-DMBA based on histopathologic changes on renal cell of cell proliferation and to observe the optimal concentration of N. sativa as antiproliferative agent. Sprague Dawley strain female rats were divided into live groups. Group 1 was given DMBA 20 mg/kg BW. Group 2, 3, 4, were given DMBA and chloroform extracts of N. sativa with 250; 500; 750 mg kg BW rank dose. Group 5 was given corn oil. Renal cell histopathology was observed by H&E and AgNOR staining. The inhibition of renal cell proliferation was observed with mAgNOR value. mAgNOR data were analyzed using Kolmogorov-Smirnov test, ANOVA and Tukey HSD. The results of H&E and AgNOR staining showed that at a dose of 7 SOmg/kg BW chloroform extract of N. sativa reduced cell damage and inhibit renal cells proliferation with mAgNOR value of 1.069. This result suggest that the chloroform extract of N. sativa had the potential effect as chemopreventive agent.